Life Events and Travel Behavior: Exploring the Interrelationship Using UK Household Longitudinal Study Data. Issue 1 (January 2014) - Clark, Ben; Chatterjee, Kiron; Melia, Steve; Knies, Gundi; Laurie, Heather
Recent research has indicated that changes in travel behavior are more likely at the time of major life events. However, much remains to be learned about the extent to which different life events trigger behavioral change and the conditions under which life events are more likely to trigger change. The UK Household Longitudinal Study (UKHLS) offers a previously unavailable opportunity to investigate this topic for a large, representative sample of the UK population. UKHLS data were also linked to local spatial data drawn from the census and other sources to elucidate the effect of the spatial context on changes to travel behavior in association with life events. Findings from an exploratory analysis of data from UKHLS Waves 1 and 2 are presented first. Transition tables demonstrate a strong association between changes in car ownership and commute mode and the following life events: employment changes, residential relocation, retirement, the birth of children, and changes in household structure. The results of logit models that relate the probability of an increase and a decrease in the number of cars owned to the occurrence of life events and that control for individual and household characteristics and spatial context are then shown. These models show, for example, that moves to urban and rural areas have contrasting effects on travel behavior and that having a new child in itself is not a significant influence on car ownership in the short term.